Methylenetetrahydrofolate reductase polymorphism, plasma homocysteine and age - Todesco, Liliane; Angst, Christian Peter; Litynski, Piotr; Loehrer, Franziska; Fowler, Brian; Haefeli, Walter E. (European journal of clinical investigation, 1999)
Background Elevated fasting levels of total homocysteine are now accepted as an independent risk factor for the development of arteriosclerotic vascular diseases. A polymorphism in the gene encoding methylenetetrahydrofolate reductase (MTHFR), caused by the C677T point mutation, leads to increased thermolability of the enzyme, with reduced enzyme activity. We studied the frequency of this mutation in different groups of the Swiss adult population. Patients and methods DNA from 361 subjects was screened for the thermolabile MTHFR variant with PCR. Included were healthy subjects without vascular disease (n = 118), older healthy subjects (n = 106), patients with coronary artery disease (CAD, n = 75), and patients with peripheral arterial occlusive disease (PAOD, n = 63). Results In the different groups studied, homozygosity for the mutation ranged from 4.8 to 16.2%, with a frequency of 16.2% in the healthy cohort. The allele frequencies of the thermolabile allele were 38.5 and 27.3 in young and old controls, and 37.3 and 33.3 in CAD and PAOD patients. In the healthy younger subjects the mutant allele was 1.4 times more frequent compared to the older subjects (P = 0.01). No difference in either MTHFR genotype distribution (P = 0.33) or allele frequencies (P = 0.48) between patients and controls was found. Except for the PAOD group with elevated tHcy levels for the +/+ carriers compared to the other genotypes, no statistically significant difference was found comparing homocysteine levels with genotype. Conclusion This study shows no link between the mutation and the occurrence of vascular disease but we found evidence pointing to a correlation between the mutation and longevity in our population.